Comparison of Vicryl, Dexon and Intestinal Stapler for the Closure of Colon in Dogs - Khalid Hussain Khan; Allah Bux Kachiwal; Shahla Karim Baloch; Rameez Raja Kaleri; Amir Nawas Khan; Mujahid Ali Shah; Gulam Murtaza Mari; Mehran Ali Baloch; Nawaz Sharif; Sajid Ali Umrani; Muhammad Zeb (Journal of Basic & Applied Sciences, 2017)
Eighteen healthy mongrel dogs of sexes, varying ages (16.50 ± 0.22 months) and weights (19.83 ± 0.16 kg) were used in this study. The experiment was conducted in the | department of Surgery and Obstetrics, Faculty of Animal Husbandry and Veterinary Sciences, Sindh Agriculture University, Tandojam.A total of 18 dogs (male and female) were randomly divided into three groups placing 6 animals in each i.e., group-A (Vicryl 3/0 suture material), B (Dexon 3/0 suture material) and C (stapler). Physically healthy animals were used in this study in order to achieve the required results. Xylazine (9.91 ± 0.08 mg/dog) and thiopental Sodium (198.33 ± 1.05 mg/dog) was administered intramuscularly in all groups. The anaesthetized animals were placed on the dorsal recumbancy on surgical table in order to perform surgical procedure. The caudal ventral midline incision of 5 cm was made in all dogs to exteriorized the colon. One incision of 5 cm was given on colon and bleeding was controlled by artery forceps. Colon incision was closed with Vicryl (3/0) in group-A, Dixon (3/0) in group-B and intestinal stapling materials in dogs of group-C. The peritoneum in each dog was sutured with chromic catgut by simple interrupted suture technique, the linea alba was sutured with chromic catgut by simple continuous suture technique, sub-cutaneous layer was apposed with sub-cuticular suture technique using 3/0 chromic catgut. Skin was closed with simple interrupted suture pattern using silk 2/0 suture material in dogs.The total duration of anesthesia required was 328.33 ± 1.17, 330.00 ± 1.39 and 313.83 ± 2.52 minutes for closure of colon closed with Vicryl, Dexon and Stapling material respectively. The mean number of total stitches for colon closure with Vicryl, Dexon and stapling material was 15 ±0.57. 17.00 ± 0.36 and 6.66 ± 0.21 respectively. Though the partial development of mucosal folds can be seen on day 10 of post-surgery whereas fully development except lamina epithelia on day 20. It is concluded that Vicryl suture material showed the superiority in terms of better apposition of the sutured tissues and better healing and lesser complications like minimal adhesions between sutured site and other structures applied with double layer appositional suture technique for the closure of colon in dogs. This study also reveals that all suture materials were not completely free from complications but staple technique showed quicker application and lesser number of staples was required as compare to Vicryl and Dexon suture stitches and duration..